Structural responses of secondary lining of high-speed railway tunnel excavated in loess ground - Zhang, Dingli (2014)
To systematically study the mechanical properties and structural responses of the secondary lining for high-speed railway tunnels excavated in loess ground, on-site monitoring was performed to measure the contact pressure between the primary lining and secondary lining. It is found that the contact pressure reaches its first peak value when the tunnel formwork carriage is removed. The load acting on secondary lining is in the form of deformation pressure, which is different from the loose pressure prescribed in the China Tunnel Design Standard. The results obtained from this study enhance our understanding towards the mechanical characteristics of secondary lining for high-speed railway tunnels and are also beneficial to secondary lining design.